Rhizobium meliloti exopolysaccharide mutants elicit feedback regulation of nodule formation in alfalfa - Caetano Anollés, Gustavo (1990)
Nodule formation by wild-type Rhizobium meliloti is strongly suppressed in younger parts of alfalfa (Medicago sativum L.) root systems as a feedback response to development of the first nodules (G Caetano-Anolles, WD Bauer [1988] Planta 175: 546-557). Mutants of R. meliloti deficient in exopolysaccharide synthesis can induce the formation of organized nodular structures (pseudonodules) on alfalfa roots but are defective in their ability to invade and multiply within host tissues. The formation of empty pseudonodules by exo mutants was found to elicit a feedback suppression of nodule formation similar to that elicited by the wild-type bacteria. Inoculation of an exo mutant onto one side of a split-root system 24 hours before inoculation of the second side with wild-type cells suppressed wild-type nodule formation on the second side in proportion to the extent of pseudonodule formation by the exo mutants. The formation of pseudonodules is thus sufficient to elicit systemic feedback control of nodulation in the host root system: infection thread development and internal proliferation of the bacteria are not required for elicitation of feedback. Pseudonodule formation by the exo mutants was found to be strongly suppressed in split-root systems by prior inoculation on the opposite side with the wild type. Thus, feedback control elicited by the wild-type inhibits Rhizobium-induced redifferentiation of host root cells.